Bioelectrochemical processes and cellulosic carbon source enhance the autotrophic and heterotrophic denitrification of low C/N ratio wastewater in tidal flow constructed wetland - Microbial fuel cells. (20th August 2022) - Zhang, Ke; Yang, Siqiao; Wang, Wei; Luo, Hongbing; Chen, Wei; Zhang, Xiaoxiao; Ma, Dandan; An, Xiaochan; Chen, Fenghui; Cheng, Lin; Chen, Jia; Mo, You; et al.
Abstract: To solve the problem of poor nitrogen and phosphorus removal efficiency of low C/N ratio wastewater, a siphon constructed wetland - microbial fuel cell (CW-MFC) reactor was constructed. And the influence of electrochemical process on autotrophic denitrification and nitrogen removal was studied. The effects of agricultural waste as cellulose carbon source on heterotrophic denitrification and electricity generation were also investigated. In addition, related electrochemical processes and microbial mechanisms were studied. The results indicated that MFC enhanced autotrophic denitrification. The addition of cellulose carbon source could significantly promote the heterotrophic denitrification process ( P  < 0.05). In 137 days, the reactor with carbon source added to both cathode and anode (CS CW-MFC) had the best removal effect on COD, NH4 + -N and TN, with removal rates of 98.38%, 79.31% and 84.43%, respectively. The removal efficiency of TP reached 89.92%. Adding carbon sources facilitated biological electricity production. The maximum voltage was 450 mV, and the maximum power density was 113.95 mW m −3 . However, methane emissions increased slightly with the addition of carbon sources. Compared with previous studies, tidal flow via siphon aeration could significantly improve TN removal efficiency. Bioelectrochemical processes had significant impact on the autotrophic denitrifying bacteria, the relative abundance of Bacteroidota and Proteobacteria was the highest. This study suggests that the addition of cellulose carbon source and the operation of tidal flow CW-MFC can enhance treatment of low C/N ratio wastewater. This technology not only enables agricultural waste to be recycled, but also improves the efficiency of sewage treatment and energy recovery. Graphical abstract: Image 1 Highlights: Bioelectrochemistry affected autotrophic denitrification and nitrogen removal. Cellulose carbon source was beneficial to heterotrophic denitrification. The addition of cellulose carbon source increased the system electricity generation. The tidal flow in CW-MFC can enhance the treatment of low C/N ratio wastewater. Autotrophic/heterotrophic denitrification and bioelectroactive bacteria coexisted.